Conversão em profundidade de dados migrados em tempo da bacia do Parnaíba - CUNHA, Antonio Rizimar de Andrade (2019)
Nowadays, the Parnaíba basin is considered by many authors as an ‘exploratory frontier’ due to many unsuccessful trials in oil exploration. For example, considering 33 wells distributed along of its extension, only three have evidences of hydrocarbons (HC). However, in geological terms, this basin is one of the most unknown basins, pondering its giant proportions. In this context, the National Petroleum Agency (NPA) has released a seismic processing project aiming to improve the knowledge about the basin. At the present work, it was applied seismic processing techniques supported by ProMAX@ software, property of the LandMark Corporation, in order to perform the depth conversion of a time-migrated section of Line 295_0007 from a time interval velocity table and retropropagation of the image ray. By this method, it is aimed to improve the quality of the seismic image, turning it more reasonable to the interpreter. The result of the time-to-depth conversion was compared to the results obtained by other authors who used different geophysical methods such as: composite well log profiles, which enable to calibrate well log data and seismic data, important factor to the identification of the most relevant seismic horizons; Bouguer Anomaly Map and the Topographic Relief of Basin Basement, which proportionate good indications of regions that have remarkable structural lows. The correlation of the seismic section with other kinds of data reinforces the results, providing more coherent geological interpretation and, consequently, a better accurate model for the studied field.